Role of A5 noradrenergic neurons in the chemoreflex control of respiratory and sympathetic activities in unanesthetized conditions - Taxini, Camila L. [UNESP]; Moreira, Thiago S.; Takakura, Ana C.; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP]; Zoccal, Daniel B. [UNESP] (Elsevier, 2017)
The A5 area at the ventrolateral pons contains noradrenergic neurons connected with other medullary areas involved in the cardiorespiratory control. Its contribution to the cardiorespiratory regulation was previously evidenced in anesthetized conditions. In the present study, we investigated the involvement of the A5 noradrenergic neurons to the basal and chemoreflex control of the sympathetic and respiratory activities in unanesthetized conditions. A5 noradrenergic neurons were lesioned using microinjections of anti-dopamine β-hydroxylase saporin (anti-DβH-SAP). After 7–8 days, we evaluated the arterial pressure levels, heart rate and minute ventilation in freely moving adult rats (280–350 g) as well as recorded from thoracic sympathetic (tSN) and phrenic nerves (PN) using the arterially perfused in situ preparation of juvenile rats (80–90 g). Baseline cardiovascular, sympathetic and respiratory parameters were similar between control (n = 7–8) and A5-lesioned rats (n = 5–6) in both experimental preparations. In adult rats, lesions of A5 noradrenergic neurons did not modify the reflex cardiorespiratory adjustments to hypoxia (7% O2) and hypercapnia (7% CO2). In the in situ preparations, the sympatho-excitation, but not the PN reflex response, elicited by either the stimulation of peripheral chemoreceptors (ΔtSN: 110 ± 12% vs 58 ± 8%, P < 0.01) or hypercapnia (ΔtSN: 9.5 ± 1.4% vs 3.9 ± 1.7%, P < 0.05) was attenuated in A5-lesioned rats compared to controls. Our data demonstrated that A5 noradrenergic neurons are part of the circuitry recruited for the processing of sympathetic response to hypoxia and hypercapnia in unanesthetized conditions.
Keywords: hypercapnia; hypoxia; noradrenergic neurons; respiration; sympathetic activity